Measuring Minorities: Reflections on the Cephalic Index - Biehler-Gomez, Lucie; Porro, Alessandro (Medicina Historica, 2025)
The cephalic index, introduced in the 19th century as an anthropometric tool for classifying cranial shapes, has had a complex and controversial history. Initially developed as a seemingly objective measure, it became a cornerstone of racial typologies and was co-opted to support socio-political ideologies that reinforced racial hierarchies. Through its application, the index perpetuated unfounded associations between cranial morphology and intellectual or moral capacities. This paper critically examines the rise, misuse, and eventual rehabilitation of the cephalic index in Italy, exploring its historical trajectory from a tool of scientific inquiry to an instrument of exclusionary ideologies and back to its contemporary medical applications. While its use today in medical diagnostics, such as cranial deformity assessments, reflects a shift towards neutral and therapeutic purposes, the legacy of its misuse serves as a cautionary tale. This study emphasizes the importance of preserving the memory of the cephalic index’s history to prevent the recurrence of its distorted applications. By reflecting on the lessons from its past, we underscore the ethical responsibilities inherent in anthropological and medical research and the need to remain vigilant against the misuse of scientific tools. The cephalic index’s journey exemplifies how science can be both a tool for understanding human diversity and, if misused, a vehicle for perpetuating bias.